Case report: Clinical experience of treating pembrolizumab-induced systemic capillary leak syndrome (SCLS) in one patient with metastatic gastroesophageal junction squamous cell carcinoma - Hua Ni; Xinjia Ding; Shikai Wu; Xuan Jin (Frontiers Media S.A., 2023)
Systemic capillary leak syndrome (SCLS) is a rare and complex adverse effect of immune checkpoint inhibitors (ICIs). The diagnosis of drug-induced SCLS is based on diffuse infusions of exudative fluid into the interstitial areas and the exclusion of other causes. The best management of ICIs-induced SCLS is not settled, though proper supportive care and corticosteroids were commonly applied as the first-line treatment. In our patient with advanced gastroesophageal junction squamous cell carcinoma, although ICIs-induced SCLS was successfully controlled with corticosteroids, the patient soon experienced cancer progress and died of pulmonary infections. Based on our experience and the reported cases by other hospitals, different stages of SCLS might respond differently to the same treatment. Therefore, a grading of ICIs-induced SCLS might help to stratify the patient for different treatment strategies. Besides, corticosteroids-sensitive patients, though waived from deadly SCLS, might be at higher risk of cancer progress and subsequent infections due to the application of corticosteroids. Considering that the inflammatory factors should be closely involved in the development of ICIs-induced SCLS, targeted therapy against the driver inflammatory cytokine might offer treatment regimens that are more effective and safer.